Lamin B1 is required for mature neuron-specific gene expression during olfactory sensory neuron differentiation - Crystal M. Gigante (Nature Portfolio, 2017)
Emerging evidence suggests that lamins regulate gene expression during cellular differentiation. Giganteet al. show that lamin B1 is necessary for the upregulation of mature neuron-specific genes during olfactory neuron differentiation, and its deficiency leads to attenuated olfactory neuron response to odour in mice.